A new conceptual framework for managing hamstring injury risk in soccer - implementing a data-informed approach: A narrative review - Pillitteri, G.; Clemente, F.; Petrucci, M.; Sarmento, H.; Figueiredo, A.; Bongiovanni, T.; Bianco, A.; Battaglia, G.; Gabbett, T. J. (Biology of Sport, 2026)
The multifactorial and complex nature of athletic injuries complicates the establishment of clear cause-and-effect relationships, making it challenging to pinpoint precise injury aetiology in the operational field. Research has explored the connection between injuries and training load (TL), identifying an association between high external loads (EL) - such as high-speed running (HSR) and sprinting - and non-contact hamstring injuries. Despite this, injury prevention remains largely ineffective, possibly reflecting a gap between scientific knowledge and practical application, as well as cognitive biases in translating research into real-world scenarios. This paper aims to: 1) summarize key findings on non-contact injuries in soccer, focusing on risk factors and the TL-injury relationship; 2) describe major conceptual frameworks and highlight cognitive biases when attributing injuries exclusively to TL; 3) propose new conceptual frameworks for non-contact injuries, with a primary focus on hamstring injuries. Using a qualitative approach, we present a multilevel causation framework that underscores the significant - but not exclusive - role of sprinting and TL in injury occurrence. We introduce two key concepts: acute mechanical load tissue exposure (AMLTE), referring to the peak acute mechanical stress a muscle can tolerate, and chronic muscle tolerance to load (CMTTL), representing the capacity to endure load over time. We aimed to support a data-informed approach to injury risk management and TL monitoring in daily practice. While we stress that TL and sprinting are not the sole causes of injury, we assert their relevance within a multifactorial model. This framework may assist professionals in developing more effective training strategies and injury prevention practices.